/d-/ as a Future Marker in the Jordanian Arabic Dialect of Irbid - Husein, Ansam Khaled; Al-Shawashreh, Ekab Yousef (Dirasat: Human and Social Sciences, 2025)
Objectives: This study investigates the emergence of an incoming future marker in the Jordanian Arabic Dialect of Irbid. Methods: Using synchronic data from the Jordanian Arabic Dialect of Irbid collected by Husein (2022) and adopting the cline of grammaticality approach that was proposed by Hopper and Traugott (2003) [content word > grammatical word > clitic > inflectional affix], the researchers propose that d- prefix (the new incoming variant) developed from bid 'will' (functional) which originally arose from the volitional verb bid 'want' (lexical) and, therefore, expresses futurity. This assumption is supported by the semantic, syntactic, and phonological changes in the grammaticalization path of d-prefix. Results: The results indicate that d-prefix, similar to bid, shows nuances of willingness and intention in the future. Since the same token that expresses willingness and intention can indicate prediction, the d- prefix is used to realize futurity in the Jordanian Arabic Dialect of Irbid. Moreover, like bid, the present data show that the d-prefix is used in both subordinate (an advanced stage in the grammaticalization path) and main clauses. Also, the results show that the d-prefix expresses futurity unambiguously. Conclusions: The findings of this study show that bid (lexical) has undergone desemanticization, erosion, and decategoralization that resulted in the emergence of d- as a future marker (via the functional bid).